Determination of Geometry and Analysis CFD Centrifugal Compressor using Supercritical Carbon Dioxide as Working Fluid - Fathoni-13114081, Akhmad
CO2 compounds turn into supercritics when they exceed their critical points (T = 304.1 K, P = 7.37 MPa). This low critical point value allows using water at room temperature as a coolant. The power generation cycle used is the Closed Brayton Cycle. The S-CO2 cycle increases efficiency by reducing the compressor's power to changes in properties when compressed near its critical point. Supercritical carbon dioxide properties that have a density close to water in the liquid phase allows the use of more compact components. Other advantages of the S-CO2 cycle include; thermodynamic properties that are familiar, non-toxic, abundant quantities, low prices, low viscosity, high molecular mass so that there is a possibility of low leakage. The advantage of this superkritic carbon dioxide makes it the potential to be used as a fluid in energy conversion systems The aims of this final project is to design a centrifugal compressor using supercritical carbon dioxide as working fluid. The mass flow rate of 2,50 kg/s, inlet total pressure and total temperature respectively of 7.8 MPa and 320.4 K, and outlet static pressure of 13.2 MPa at 70.000 rpm was used as known parameters. Meanline analysis obtained total-to-total efficiency of 71,8% and power of 70,41 kW with rotor diameter of 27 mm and contains 12-pieces of blade. After a spesific compressor was designed and analyzed using meanline analysis, the flow was analyzed using ANSYS-CFX, a three-dimensional Computational Fluid Dynamics (CFD) code. CFD result are in fairly good agreement with meanline analysis. CFD analysis show that the designed compressor is needs power 77,92 kW with total-to-total efficiency of 69,32 % .